จิตวิญญาณและการฟื้นฟูชีวิต: บทเรียนแผ่นดินไหวสำหรับแรงงานผู้เปราะบางทางสังคม - (ฉัตรชัย สุฉตฺตชโย), พระราชวชิรญาณเมธี (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
This academic article aims to explore the dimensions of spirituality and the restoration of life among socially vulnerable laborers through the lens of an earthquake disaster, regarded as both an emotional and structural lesson at the individual and systemic levels. The study applies key Buddhist principles—such as the law of dependent origination (Idappaccayata or Paticcasamuppada), the four noble truths, and the noble eightfold path—together with contemplative education concepts to understand the inner mechanisms of healing, suffering, and the return to balance. The truths employed in post-disaster recovery are not confined to material or economic dimensions; rather, they must encompass the restoration of human dignity and worth. Vulnerable laborers are often socially marginalized and deprived of opportunities for meaningful participation. Therefore, effective recovery and healing processes require an integrative approach that combines Buddhist principles with modern social work concepts, such as psychosocial therapy, empowerment, and the revitalization of social and spiritual capital. The data synthesized in this study highlight a sustainable recovery model—addressing physical, mental, and spiritual dimensions—based on an integrative framework of Buddhist Studies and Social Work, both at policy and practice levels, to promote recovery processes grounded in an understanding of suffering, happiness, and life purpose in contemporary society.   Keywords : Spiritual Restoration, Earthquake Lessons, Socially Vulnerable Laborers